INSPIRASI 'THE LEGEND OF THE BLUE SEA' DALAM PENERAPAN PADA TEKNIK TEKSTIL MANIPULATION - Rafaela Pasca Hariyanto; Christabel Annora Paramita Parung; Siti Zahro (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2023)
The Covid-19 pandemic is a problem occured throughout the world and has an impact, especially on Indonesia. One of the consequences is the cultural change that occurred during before the pandemic, during the pandemic, and after the pandemic. Seeing the drastic cultural changes, it reminds of the Korean drama